The method for impact analyzing of duplex plasma nitriding and DLC coatings on the cyclic performance of 16MnCr5 piston pin steel under plain and fretting fatigue testing - Mobin Dizisaz; Mohammad Sadegh Aghareb Parast; Mohammad Azadi (MethodsX)
The current analysis studied the analyzing method and experimental datasets of the plain and fretting fatigue lifetime of 16MnCr5 steels and the impact of duplex plasma nitriding and diamond-like carbon (DLC) coatings. Standard specimens were cut from industrial piston pins used in combustion engines and machined for this objective. Subsequently, plain and fretting fatigue tests, with a fretting force of 15 N, were performed on both as-received and DLC-coated specimens at stress levels ranging from 250 to 550 MPa and under a frequency of 100 Hz. The impact of the mentioned parameters on the fatigue behavior of the samples was carefully analyzed using regression models to identify the influential or significant factors. • Fully reversed rotary bending plain and fretting fatigue testing was conducted at stress levels ranging from 250 to 550 MPa. The fatigue lifetime of the coated samples increased by 47.7 % under pure fatigue conditions and by 85.3 % under fretting fatigue conditions, respectively. • OM and Raman spectroscopy were used to investigate the microstructure and the DLC coating. The thickness of the DLC coating was measured at 1.956± 0.1478 micrometers, while the thickness of the white layer was 4.4248± 0.5020 micrometers. • Obtained fatigue data were analyzed in Design-Expert software using the Poisson method and the linear regression (no transform) method. In the results of the Poisson regression model for all fatigue data, the McFadden Pseudo R² was 94.92 %, and the Adjusted McFadden Pseudo R² was also 94.92 %. For the linear regression model analyzing all logarithmic fatigue data, the R² was 92.87 %, the Adjusted R² was 90.75 %, and the Predicted R² was 82.76 %.